CRAFTING TEST-DRIVEN SOFTWARE WITH PYTHON write test suites that scale with your applications... needs and complexity, using python and pytest. - MOLINA, ALESSANDRO (PACKT PUBLISHING LIMITED, 2021)
This practical guide to test-driven development will help developers working with Python put their knowledge to work. You'll learn how to adopt an effective test-driven approach to Python software development with WebTest and web frameworks. The book is filled with hands-on examples to enable you to write reliable test suites to ensure your ...